Поиск мультинейтронов в кластерном распаде ядер 238U; Известия вузов. Физика; Т. 56, № 11-2 - Варлачев (Варлачёв) В. А. Валерий Александрович; Гарапацкий А. А. Александр Александрович; Дудкин Г. Н. Геннадий Николаевич; Кузнецов С. И. Сергей Иванович; Падалко В. Н. Владимир Николаевич; Тураев Н. С. Николай Степанович (2013, 2013)
Заглавие с экрана